A novel lumen-apposing metal stent for endoscopic ultrasound-guided drainage of pancreatic fluid collections: a prospective cohort study - Walter, Daisy; Will, Uwe; Sanchez-Yague, Andres; Brenke, Dirk; Hampe, Jochen; Wollny, Helge; López-Jamar, Jose Miguel Esteban; Jechart, Gertrud; Vilmann, Peter; Gornals, Joan B.; Ullrich, Sebastian; Fähndrich, Martin; de Tejada, Alberto Herreros; Junquera, Félix; Gonzalez-Huix, Ferran; Siersema, Peter D.; Vleggaar, Frank P. (Endoscopy, 2015)
Background and study aims: A novel large-diameter, lumen-apposing, self-expanding metal stent with bilateral flanges was recently developed for endoscopic ultrasound (EUS)-guided transmural drainage of symptomatic pancreatic fluid collections (PFCs). The aim of this study was to evaluate the efficacy and safety of this stent in a large cohort. Patients and methods: Patients with a PFC undergoing EUS-guided drainage with this novel stent were prospectively enrolled in this multicenter cohort study. Results: There were 61 patients: 46 patients (75 %) with walled-off necrosis (WON) and 15 (25 %) with a pancreatic pseudocyst. Stent placement was technically successful in 60 patients (98 %, 95 %CI 95 % – 100 %). Clinical success, defined as resolution of clinical symptoms in combination with a decrease in the PFC size to ≤ 2 cm on imaging, was achieved in 93 % of patients with a pancreatic pseudocyst (95 %CI 77 % – 100 %) and in 81 % of patients with WON (95 %CI 69 % – 94 %). Treatment failure occurred in nine patients (16 %, 95 %CI 6 % – 26 %), including four patients who required surgical intervention. Stent removal was performed in 82 % of patients after a median of 32 days (range 2 – 178) and was rated as easy in all but one patient. In 10 patients, endoscopic stent removal was not performed because of stent migration (n = 3), stent dislodgement during necrosectomy (n = 3), stent removal during surgery (n = 2), or refusal by the patient (n = 2). In total, five major complications were reported (9 %, 95 %CI 2 % – 16 %), including PFC infection (n = 4) and perforation (n = 1). Conclusion: EUS-guided drainage using this novel stent is feasible and the clinical results obtained are promising with a low major complication rate.